Shareholders’ Lawsuit in Georgian Legislation and Case Law - Jinoria, Khatuna (European Scientific Journal, ESJ, 2021)
Obtaining shares in a joint stock company grants the owner important rights and imposes several obligations on them. In the list of shareholders’ rights, one of the most important subjects is the right to sue the shareholder’s lawsuit. The right to bring in front of courts certain aspects of company-related activities is the legal mechanism of protecting the shareholders other rights. Shareholders’ lawsuit plays an important role in the protection of minority shareholders. Shareholders’ lawsuit also includes two types of legal actions: direct lawsuit and derivative lawsuit. Georgian case law is not very advanced in this area. When shareholders bring matters in front of courts, the number of precedents adhered to is rare. As for the derivative lawsuit, the relative novelty of this legal institution in Georgian legislation causes the lack of deeper understanding. Georgian doctrine does not provide thorough analysis of legal nature and divergence of shareholders’ lawsuits when it comes to case law. As mentioned above, it is quite scarce.